2014
DOI: 10.1063/1.4890840
|View full text |Cite
|
Sign up to set email alerts
|

Direct printing and reduction of graphite oxide for flexible supercapacitors

Abstract: We report direct printing and photo-thermal reduction of graphite oxide (GO) to obtain a highly porous pattern of interdigitated electrodes, leading to a supercapacitor on a flexible substrate. Key parameters optimized include the amount of GO delivered, the suitable photo-thermal energy level for effective flash reduction, and the substrate properties for appropriate adhesion after reduction. Tests with supercapacitors based on the printed-reduced GO showed performance comparable with commercial supercapacito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…rGO can be produced by variousp rocesses, but they currently require high-temperatures or are prohibitively timeconsuming. [27] Jung et al employed ax enon camera flash, [28] but this method provede xtremelys ensitive to GO/substrate wetting, since a number of substrates produced GO droplets of various contact angles, at endency critical to rGO development as GO undergoes volume expansion during reduction.G uan et al used a picosecond laser in al iquid nitrogen environmentt of abricate porousrGO from GO sheets. [24,25] Jiang et al used annealing in H 2 /Ar at 300 8Cf or 2h [26] and Tian et al used H 2 plasma at 425 8C.…”
Section: Introductionmentioning
confidence: 99%
“…rGO can be produced by variousp rocesses, but they currently require high-temperatures or are prohibitively timeconsuming. [27] Jung et al employed ax enon camera flash, [28] but this method provede xtremelys ensitive to GO/substrate wetting, since a number of substrates produced GO droplets of various contact angles, at endency critical to rGO development as GO undergoes volume expansion during reduction.G uan et al used a picosecond laser in al iquid nitrogen environmentt of abricate porousrGO from GO sheets. [24,25] Jiang et al used annealing in H 2 /Ar at 300 8Cf or 2h [26] and Tian et al used H 2 plasma at 425 8C.…”
Section: Introductionmentioning
confidence: 99%
“…5e along with recently reported state-of-the-art printed MSC devices. 10,11,21,29,43,[51][52][53][54][55][56][57][58][59][60] The energy density values of RArG-4-200 MSC range from 4.5 to 18.8 mW h cm À3 , with corresponding power densities in the range of 0.5 to 40.9 W cm À3 . This energy storage capability is notably higher than that of commercial lithium thin-film batteries, 2 and is superior to those of recently reported MSC devices based on alternative electrochemical active materials including carbon (0.2-9.1 mW h cm À3 ), metal oxides (0.7-1.4 mW h cm À3 ) and conducting polymers (3 mW h cm À3 ) fabricated by various printing techniques.…”
Section: Resultsmentioning
confidence: 99%
“…These performance metrics are comparable with commercial supercapacitors. [138] Chi et al developed an all-solid-state symmetric supercapacitor based on inkjet printing a graphene hydrogelloaded polyanilic (GH-PANI) electrode, to give a power density of 0.4 kW kg −1 and energy density of 24.02 Wh kg −1 . [139] Li et al demonstrated that that printing graphene/DMF dispersions as inks on the fingers of an interdigitated structure in a symmetric supercapacitor delivers a reasonably high areal power density of 8.8 mW cm −2 .…”
Section: D Printed Supercapacitorsmentioning
confidence: 99%